2021
DOI: 10.1021/jacs.1c01620
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Photogenerated Molecular Quartet States as Spin Qubits and Qudits

Abstract: Photogenerated molecular spin systems hold great promise for applications in quantum information science because they can be prepared in well-defined spin states at modest temperatures, they often exhibit long coherence times, and their properties can be tuned by chemical synthesis. Here, we investigate a molecular spin system composed of a 1,6,7,12-tetra(4-tert-butylphenoxy)perylene-3,4:9,10-bis(dicarboximide) (PDI) chromophore covalently linked to a stable nitroxide radical (TEMPO) by optical and electron pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 71 publications
(107 reference statements)
8
91
1
1
Order By: Relevance
“…Compared to PDI 4sg –TEMPO, the fsTA data of which was already published previously, 36 the deactivation of the excited singlet state is found to be faster in PDI 0sg –TEMPO by a factor of about four. The S 1 state deactivation is also accelerated (by a factor of roughly two) when attaching a second TEMPO radical to the system in PDI 4sg –(TEMPO) 2 .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Compared to PDI 4sg –TEMPO, the fsTA data of which was already published previously, 36 the deactivation of the excited singlet state is found to be faster in PDI 0sg –TEMPO by a factor of about four. The S 1 state deactivation is also accelerated (by a factor of roughly two) when attaching a second TEMPO radical to the system in PDI 4sg –(TEMPO) 2 .…”
Section: Resultssupporting
confidence: 65%
“…5 shows a comparison of the field-swept echo-detected EPR spectra recorded for PDI 0sg –TEMPO and PDI 4sg –TEMPO in frozen toluene solution at the Q-band after light irradiation at 535 nm. PDI 4sg –TEMPO was previously characterized by pulse EPR spectroscopy 36 and its transient EPR spectrum could be assigned to the trip-quartet state of PDI 4sg –TEMPO by transient nutation experiments. The rather unusual, complex central feature was shown to arise from an additional splitting of the quartet sublevels by the hyperfine interaction of the 14 N nucleus of the TEMPO moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Controlling spin–spin interactions in multispin molecular assemblies beyond the SCRP is important for using molecular spin systems for quantum information processing. Recent studies have shown that the interaction of SCRPs ,, as well as photogenerated spin-polarized triplet states with stable radicals can produce quartet states in which the interactions between the three spins can be manipulated using microwave pulses. This is a topic that is expanding rapidly and promises to provide a pathway to entanglement of multiple electron spins in molecular systems, which will greatly extend the capability of molecular systems to engage in complex quantum operations.…”
Section: Emergence Of Spin-correlated Radical Pairs As Spin-qubit Pairsmentioning
confidence: 99%
“…Condensation of a D−A unit with a radical as a qubit has been recently achieved. 64,77 In our case, where pulses separately addressing the photogenerated radical and the permanent qubit are required, transition metal-based qubits with long coherence 42,44−58 are preferred because of their g value differing from 2, as discussed above.…”
Section: F) Coupled To a By (Isotropic) Hyperfine Interaction • S Imentioning
confidence: 99%